Solar thermochemical production of ammonia from water, air and sunlight: thermodynamic and economic analyses - Michalsky, Ronald; Parman, Bryon J.; Amanor-Boadu, Vincent; Pfromm, Peter H. (My University, 2012)
Ammonia is an important input into agriculture and is used widely as base chemical for the chemical industry. It has recently been proposed as a sustainable transportation fuel and convenient one-way hydrogen carrier. Employing typical meteorological data for Palmdale, CA, solar energy is considered here as an inexpensive and renewable energy alternative in the synthesis of NH[subscript 3] at ambient pressure and without natural gas. Thermodynamic process analysis shows that a molybdenum-based solar thermochemical NH[subscript 3] production cycle, conducted at or below 1500 K, combined with solar thermochemical H[subscript 2] production from water may operate at a net-efficiency ranging from 23 to 30% (lower heating value of NH[subscript 3] relative to the total energy input). Net present value optimization indicates ecologically and economically sustainable NH[subscript 3] synthesis at above about 160 tons NH[subscript 3] per day, dependent primarily on heliostat costs (varied between 90 and 164 dollars/m²), NH[subscript 3] yields (ranging from 13.9 mol% to stoichiometric conversion of fixed and reduced nitrogen to NH[subscript 3]), and the NH[subscript 3] sales price. Economically feasible production at an optimum plant capacity near 900 tons NH[subscript 3] per day is shown at relative conservative technical assumptions and at a reasonable NH[subscript 3] sales price of about 534 ± 28 dollars per ton NH[subscript 3].
Keywords: Hydrogen; Methane; Fertilizer; Solar; Electricity; Economics; Infrastructure